2004
DOI: 10.1590/s0041-87812004000400009
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride-associated male infertility

Abstract: Finasteride is a potent and specific inhibitor of the 5α-reductase enzyme in men. Clinical studies have shown that finasteride 1mg/day is effective for promoting hair growth in men with male pattern hair loss. However, there is a concern about the use of finasteride, especially in young fertile patients, because of its action on testosterone metabolism. This paper describes 3 cases of young patients who had very poor seminal quality during finasteride treatment (1 mg/day), and their seminal quality greatly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…In contrast, a report of two infertile males with severe oligospermia or azoospermia demonstrated that 6 months after finasteride was discontinued, sperm concentration significantly improved . Another report of three cases demonstrated abnormal sperm motility and concentration while taking finasteride 1 mg/day, reversed or improved after 3–4 months . One case report showed that after 3 months of discontinuing finasteride, sperm DNA fragmentation index significantly reduced, indicating an association between the use of finasteride and sperm DNA damage .…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, a report of two infertile males with severe oligospermia or azoospermia demonstrated that 6 months after finasteride was discontinued, sperm concentration significantly improved . Another report of three cases demonstrated abnormal sperm motility and concentration while taking finasteride 1 mg/day, reversed or improved after 3–4 months . One case report showed that after 3 months of discontinuing finasteride, sperm DNA fragmentation index significantly reduced, indicating an association between the use of finasteride and sperm DNA damage .…”
Section: Resultsmentioning
confidence: 96%
“…Minoxidil is a popular hair growth promoting drug, but it is reported that it can cause adverse dermatological effects such as pruritis, dryness, scaling, local irritation, dermatitis (DeVillez, 1990). Finasteride is also a widely used hair growth promoting drug for androgenic alopecia patients, which is not recommended for female patients (Glina et al, 2004;Kaufman et al, 1998). It is reported that minoxidil is efficacious in promoting hair growth in patients with androgenic alopecia by inducing hair follicles to undergo transition from the early to late anagen phase (Gregoriou et al, 2010;Tsuboi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the investigators concluded that spermatogenesis was not adversely affected by the drug; however, they targeted only ''fertile'' male patients, excluding patients with, for example, abnormal screening semen analysis, history of infertility, cryptorchidism, and varicocele. To date, two case reports have suggested that 1 mg finasteride is associated with male infertility (7,8). Glina et al reported three cases of young patients who had very poor seminal quality during 1-mg finasteride treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has reported the effect of 1 mg finasteride. This double-blind, placebo-controlled multicenter study included only healthy men with normal spermatogenesis and did not show any effect on semen parameters (6); however, two case reports have described patients with impaired spermatogenesis that was reversed after the cessation of 1 mg finasteride (7,8). In this case report, we describe a male patient who consulted our clinic for infertility and showed almost total azoospermia during treatment with 1 mg finasteride.…”
mentioning
confidence: 98%